Why information management is vital? / Nur Asyikin Sanen and Nor Sahira Haji Jamaluddin - Sanen, Nur Asyikin; Jamaluddin, Nor Sahira (Faculty of Information Management, 2015)
This article shows an abstract of the importance of information management in our life. It includes why we need to manage the information, the problems and challenges regarding information management, how we recognize the good information, and information management and lifelong learning.